Phase diagram of polymerizing nitrogen – a theoretical prediction - Yakub, L. N. (Recent Contributions to Physics, 2015)
Polymerization of nitrogen molecules in both solid and liquid phases, which was discovered in dynamic and static experiments, and predicted in ab initio simulations, stimulated discussion on a new configurationof phase diagram of nitrogen at high pressures. We consider the high-pressure phase diagram of solid nitrogen, which has long been discussed in theoretical studies, and only in the last decade began toinvestigate experimentally.
Keywords: Nitrogen; the phase diagram; the pressure polymerization.